Learning Strategies in Acquiring Instructional Vocabulary among Pre-service English Teachers - Wiraningsih, Putu; Manik, Ni Putu Ines Marylena Candra; Budiarte, Agus (Journal of English Language and Education, 2026)
This study investigated the vocabulary learning strategies (VLS) employed by 47 pre-service English teachers enrolled in the Instructional Vocabulary course. This study employed a mixed-method design by combining quantitative data from questionnaires and qualitative data from interviews to provide a more comprehensive understanding of students’ strategy use. Using Schmitt’s (1997) taxonomy as an analytical framework, the findings showed that participants used various strategies, with cognitive strategies being the most dominant (32%), reflecting their practical and task-focused approach to vocabulary learning. Metacognitive (22%) and determination strategies (18%) were used moderately, while memory (15%) and social strategies (13%) appeared less frequently, indicating limited reflective and collaborative learning in vocabulary acquisition. Qualitative interview data revealed that students’ strategy preferences were influenced by their learning goals, course requirements, and individual learning styles. The study concludes that although participants demonstrated awareness of multiple strategy types, they still require explicit instruction and guided practice.